2023
DOI: 10.1001/jamanetworkopen.2023.32813
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Reactogenicity of Coadministration of COVID-19 and Influenza Vaccines

Tal Gonen,
Noam Barda,
Keren Asraf
et al.

Abstract: ImportanceCOVID-19 and seasonal influenza vaccines were previously given separately, although their coadministration is warranted for vaccination adherence. Limited data on their coadministration have been published.ObjectiveTo compare the reactogenicity and immunogenicity of COVID-19 and influenza vaccinations administered together with those of COVID-19 vaccination alone.Design, Setting, and ParticipantsThis prospective cohort study included health care workers at a large tertiary medical center in Israel wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…Additionally, previous research also suggested that the combined administration of the COVID-19 vaccine and the influenza vaccine is safe [ 34 , 35 ]. Therefore, as per the WHO recommendation, combined vaccination was a feasible option to increase coverage rates [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous research also suggested that the combined administration of the COVID-19 vaccine and the influenza vaccine is safe [ 34 , 35 ]. Therefore, as per the WHO recommendation, combined vaccination was a feasible option to increase coverage rates [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“… 32–34 On the other hand, three non-randomized studies conducted in healthcare workers showed between 16% and 25% reductions in anti-S antibodies when mRNA-1273 or BNT162b2mRNA was co-administered with QIVs. 37 , 38 , 40 Two of the studies used a preference-based study design that allowed individuals to choose if they received co-administered QIV. An observational study of vaccine efficacy that also used a preference-based design showed that co-administration had no effect on the risk of breakthrough SARS-CoV-2 infections.…”
Section: Discussionmentioning
confidence: 99%
“… The results support co-administration recommendations Radner et al 37 Open label, non-randomized Co-administration vs administration alone Healthcare workers mRNA (Pfizer- BioNtech) Inactivated quadrivalent Descriptive 24% decrease in anti-S titers Reactogenicity was similar in the COVID-19 alone and co-administration groups and lower in the influenza vaccine alone group. Concomitant administration raised no safety concerns but provides evidence of reduced immunogenicity Gonen et al 38 Prospective cohort Self-selected for co-administration Healthcare workers mRNA (Pfizer- BioNtech) Inactivated quadrivalent Descriptive 16% decrease in anti-S titers Reactogenicity was similar in the COVID-19 alone and co-administration groups and lower in the influenza vaccine alone group. Reactogenicity and immunogenicity were mostly unchanged with co-administration Moscara et al 39 Prospective observational Self-selected for co-administration Healthcare workers mRNA (Pfizer-BioNtech) Cellular inactivated quadrivalent Effectiveness against symptomatic SARS-CoV-2 infection Not assessed Reactogenicity was similar in the COVID-19 alone and co-administration cohorts and lower in those who received influenza vaccine alone.…”
Section: Discussionmentioning
confidence: 99%
“…A 2022 systematic review of the safety and immunogenicity of coadministered influenza and COVID-19 vaccines did not identify evidence of immune interference, 3 but this conclusion was based on data from only three studies. 4 , 5 , 6 Subsequent coadministration studies have yielded inconsistent results, but differences between groups were minimal, 7 , 8 , 9 , 10 and most studies compared vaccine coadministration with single vaccine administration rather than sequential vaccination (i.e., with an interval of 1–2 weeks between doses). 5 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 , 6 Subsequent coadministration studies have yielded inconsistent results, but differences between groups were minimal, 7 , 8 , 9 , 10 and most studies compared vaccine coadministration with single vaccine administration rather than sequential vaccination (i.e., with an interval of 1–2 weeks between doses). 5 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%